Mass Balance and Climate History of a High-Altitude Glacier, Desert Andes of Chile - Kinnard, Christophe; Ginot, Patrick; Surazakov, Arzhan; MacDonell, Shelley; Nicholson, Lindsey; Patris, Nicolas; Rabatel, Antoine; Rivera, Andres; Squeo, Francisco A. (Frontiers in Earth Science, 2020)
Glaciers in the dry Chilean Andes provide important ecological services, yet their mass-balance response to past and ongoing climate change has been little studied. This study examines the recent (2002-2015), historical (1955-2005) and past (<1900) mass-balance history of the high-altitude Guanaco Glacier (29.34ºS, >5000 m), using a combination of glaciological, geodetic, and ice core observations. Mass balance has been predominantly negative since 2002. Analysis of mass-balance and meteorological data since 2002 suggests that mass balance is currently mostly sensitive to precipitation variations, while low temperatures, aridity and high solar radiation and wind speeds cause large sublimation losses and limited melting. Mass balance reconstructed by geodetic methods shows that Guanaco Glacier has been losing mass since at least 1955, and that mass loss has increased over time until present. An ice core recovered from the deepest part of the glacier in 2008 revealed that the glacier is cold-based with a -5.5ºC basal temperature and a warm reversal of the temperature profile above 60-m depth attributed to the recent atmospheric warming trend. Detailed stratigraphic and stable isotope analyses of the upper 20 m of the core revealed seasonal cycles in the δ18O and δ2H records with periods varying between 0.5 and 3 m. w.e. a-1. Deuterium excess values larger than 10 ‰ suggest limited post-depositional sublimation, while the presence of numerous refrozen ice layers indicate significant summer melt. Tritium concentration in the upper 20 m of the core was very low, while 210Pb was undetected, indicating that the glacier surface in 2008 was at least 100 years old. Taken together, these results suggest that Guanaco Glacier formed under drastically different climate conditions than today, with humid conditions causing high accumulation rates, reduced sublimation and increased melting. Reconstruction of mass balance based on correlations with precipitation and streamflow records show periods of sustained mass gain in the early 20th century and the 1980s, separated by periods of mass loss. The southern migration of the South Pacific Subtropical High over the course of the 20th and 21st centuries is proposed as the main mechanism explaining the progressive precipitation starvation of glaciers in this area.